Dysregulation of complement factor H in juvenile-onset systemic lupus erythematosus patients - Eman Eissa; Botros Morcos; Dalia Dorgham; Naglaa Kholoussi (Archives of Rheumatology, 2022)
Objectives: This study aims to evaluate the expression pattern of factor H in peripheral blood and the frequency of factor H autoantibodies in plasma of juvenile-onset systemic lupus erythematosus (jSLE) patients compared to healthy controls. Patients and methods: Between March 2019 and October 2019, a total of 30 healthy individuals (3 males, 27 females; mean age: 26±7.4 years; range, 18 to 40 years) and 65 jSLE patients (age of onset ≤16 years) (2 males, 63 females; mean age: 23.4±7 years; range, 15 to 38 years) were included. Factor H expression pattern was examined in blood of all subjects using quantitative real-time polymerase chain reaction and the frequency of factor H autoantibodies was estimated in plasma using enzyme-linked immunosorbent assay. Results: Factor H expression was significantly downregulated in jSLE patients compared to healthy controls (p<0.01). A significant underexpression of factor H was observed in jSLE patients with nephritis compared to those without nephritis (p<0.03), while there was no association of factor H expression levels with any of the other clinical and serological features, disease activity or disease damage index of patients. Only 5% of jSLE patients were positive for factor H autoantibodies without any correlations with the clinical data or disease activity of patients. Conclusion: Our study results suggest that factor H expression can be dysregulated in jSLE patients.